Learn more about

Refine search

Results (displaying matches 1-50 of 725) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
277.a.277.2 277.a \(y^2 + y = x^5 - 9x^4 + 14x^3 - 19x^2 + 11x - 6\) $\mathrm{USp}(4)$ 0
847.a.847.1 847.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^3 + x^2\) $G_{3,3}$ 1
961.a.961.2 961.a \(y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 8x^4 + 12x^3 - 18x^2 + 12x - 7\) $G_{3,3}$ 0
961.a.961.3 961.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4 + x^3 - x - 1\) $G_{3,3}$ 0
961.a.923521.1 961.a \(y^2 + (x^3 + x^2 + 1)y = -5x^4 + 4x^3 + 3x^2 - 2x - 3\) $G_{3,3}$ 0
968.a.1936.1 968.a \(y^2 + y = x^6 - x^4\) $G_{3,3}$ 1
968.a.234256.1 968.a \(y^2 + x^3y = 6x^4 + 47x^2 + 121\) $G_{3,3}$ 1
1077.b.1077.1 1077.b \(y^2 + x^3y = x^5 + x^4 - x - 2\) $\mathrm{USp}(4)$ 0
1109.c.1109.1 1109.c \(y^2 + (x^3 + x)y = x^5 - 2x^3 - 2x^2 - 1\) $\mathrm{USp}(4)$ 0
1164.a.1164.1 1164.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - 1\) $\mathrm{USp}(4)$ 0
1210.a.1210.1 1210.a \(y^2 + (x^3 + x)y = 3x^3 - 2x^2 + 6x + 2\) $G_{3,3}$ 0
1331.a.1331.1 1331.a \(y^2 + x^3y = -x^4 - x^3 + 2x^2 + 3x + 1\) $N(G_{1,3})$ 1
1532.a.1532.1 1532.a \(y^2 + (x^3 + 1)y = -x - 1\) $\mathrm{USp}(4)$ 0
1573.a.1573.1 1573.a \(y^2 + x^3y = -x^4 - 3x^3 - 4x^2 - 3x - 1\) $G_{3,3}$ 1
1573.a.190333.1 1573.a \(y^2 + x^3y = -7x^4 - 7x^3 + 38x^2 + 21x - 83\) $G_{3,3}$ 1
1589.a.1589.1 1589.a \(y^2 + y = x^5 + 4x^4 + 4x^3 - x^2 - x\) $\mathrm{USp}(4)$ 0
1665.a.1665.1 1665.a \(y^2 + (x^3 + x^2 + 1)y = x^4 + x^3 + 2x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
1791.a.5373.1 1791.a \(y^2 + y = 3x^5 + 6x^4 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
1835.b.1835.1 1835.b \(y^2 + x^3y = -2x^4 + 4x^2 - x - 2\) $\mathrm{USp}(4)$ 0
1844.b.29504.1 1844.b \(y^2 + (x^2 + x + 1)y = -x^5 + 2x^4 - 5x^3 + x\) $\mathrm{USp}(4)$ 0
1923.a.1923.1 1923.a \(y^2 + (x^3 + x + 1)y = -x^6 + x^5 - 3x^4 + 2x^3 - 3x^2 + x - 1\) $\mathrm{USp}(4)$ 0
1936.a.1936.1 1936.a \(y^2 + y = -x^6 + 2x^4 - x^2\) $G_{3,3}$ 1
1936.b.1936.1 1936.b \(y^2 + y = -x^6 - x^4\) $G_{3,3}$ 0
1936.b.234256.1 1936.b \(y^2 + x^3y = -6x^4 + 47x^2 - 121\) $G_{3,3}$ 0
1989.a.1989.1 1989.a \(y^2 + (x^3 + x^2 + x + 1)y = -x - 1\) $\mathrm{USp}(4)$ 0
1996.a.31936.1 1996.a \(y^2 + (x^3 + 1)y = x^4 + x^3 + x^2 + 4x + 3\) $\mathrm{USp}(4)$ 0
2001.b.2001.1 2001.b \(y^2 + (x^3 + x + 1)y = x^5 - 2x^3 + x - 1\) $\mathrm{USp}(4)$ 0
2166.a.6498.1 2166.a \(y^2 + (x^3 + x)y = x^5 + 3x^4 + 3x^3 - 15x - 9\) $G_{3,3}$ 0
2261.a.2261.1 2261.a \(y^2 + y = x^5 + x^2 + x\) $\mathrm{USp}(4)$ 0
2348.a.2348.1 2348.a \(y^2 + (x^2 + x + 1)y = -x^5 - x^2 - x\) $\mathrm{USp}(4)$ 0
2445.a.22005.1 2445.a \(y^2 + y = x^5 + 4x^4 - 4x^3 + 3x^2 - x\) $\mathrm{USp}(4)$ 0
2500.a.400000.1 2500.a \(y^2 + (x^3 + 1)y = -2x^6 - 2x^5 + 2x^3 - 2x - 2\) $J(E_1)$ 0
2540.a.2540.1 2540.a \(y^2 + (x^2 + x + 1)y = x^5 + 2x^4 + x^3 + x^2\) $\mathrm{USp}(4)$ 0
2613.a.2613.1 2613.a \(y^2 + y = x^5 + x^4 - x^2\) $\mathrm{USp}(4)$ 0
2677.a.2677.1 2677.a \(y^2 + y = x^5 + 4x^4 + 4x^3 + 3x^2 + x\) $\mathrm{USp}(4)$ 0
2722.a.2722.1 2722.a \(y^2 + (x^3 + x)y = -x^4 - x - 1\) $\mathrm{USp}(4)$ 0
3061.a.3061.1 3061.a \(y^2 + (x + 1)y = -x^6 - x^5\) $\mathrm{USp}(4)$ 0
3088.a.12352.1 3088.a \(y^2 + x^3y = x^3 + 2x^2 + 2x + 1\) $\mathrm{USp}(4)$ 1
3098.a.3098.1 3098.a \(y^2 + (x + 1)y = x^5\) $\mathrm{USp}(4)$ 0
3109.a.3109.1 3109.a \(y^2 + (x^3 + x)y = -x^4 - x\) $\mathrm{USp}(4)$ 1
3125.a.3125.1 3125.a \(y^2 + y = x^5\) $F_{ac}$ 0
3189.a.3189.1 3189.a \(y^2 + (x + 1)y = x^6 + x^5\) $\mathrm{USp}(4)$ 1
3211.b.3211.1 3211.b \(y^2 + x^3y = x^5 - 4x^3 - 3x^2 + 3x + 2\) $\mathrm{USp}(4)$ 0
3313.a.3313.1 3313.a \(y^2 + (x^3 + x^2 + 1)y = -x^2 - x + 1\) $\mathrm{USp}(4)$ 0
3364.a.215296.1 3364.a \(y^2 + (x^3 + 1)y = x^5 + 4x^4 + 5x^3 + 4x^2 + x\) $G_{3,3}$ 1
3388.a.13552.1 3388.a \(y^2 + y = x^6 - 4x^4 + 5x^2 - 2\) $G_{3,3}$ 1
3436.a.3436.1 3436.a \(y^2 + (x^2 + x + 1)y = -x^5\) $\mathrm{USp}(4)$ 0
3483.a.282123.1 3483.a \(y^2 + y = x^5 - x^4 - 2x^3 + x^2 - x\) $\mathrm{USp}(4)$ 1
3566.b.3566.1 3566.b \(y^2 + xy = x^5 - x^4 + 4x^3 - 8x^2 + 5x - 1\) $\mathrm{USp}(4)$ 0
3601.a.3601.1 3601.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 + x^2 - x + 1\) $\mathrm{USp}(4)$ 0
Next

Download all search results for